Flexible power and hydrogen production: Finding synergy between CCS and variable renewables - Schalk Cloete; Lion Hirth (ZBW – Leibniz Information Centre for Economics, 2019)
Capital-intensive CO2 capture plants become uneconomical at the low running hours implied by a renewables-based power system. To address this challenge, the novel gas switching reforming (GSR) power and hydrogen plant was recently proposed. When electricity is scarce, GSR generates power. When electricity is abundant, rather than shutting down, GSR keeps operating and produces hydrogen instead, maintaining a high capacity factor for all CO2 capture, transport, and storage infrastructure. This study assesses the interplay between this flexible GSR technology and variable renewables using a power system model. The model optimizes investment and hourly dispatch of 13 different technologies to minimize total system costs. Results show that the inclusion of GSR brings substantial benefits relative to conventional CO2 capture. When a CO2 price of exteuro100/ton is implemented, inclusion of GSR increases the optimal wind and solar share from 32% to 47%, lowers total system costs by 8%, and reduces total system emissions from 45 to 4 kgCO2/MWh. In addition, GSR produces clean hydrogen equivalent to about 90% of total electricity demand, which can be used to decarbonize transport and industry. GSR could therefore become a key enabling technology for a decarbonization effort led by wind and solar power.
Additional information: Please cite as: Cloete, Schalk & Lion Hirth (2020): “Flexible power and hydrogen production: Finding synergy between CCS and variable renewables”, Energy 192, https://doi.org/10.1016/j.energy.2019.116671.
Keywords: 330